0385 Bias in Exposure Assessment from Worst-Case Selection of Workplaces in OSHA's Integrated Management Information System Databank IMIS. (23rd June 2014) - Sarazin, Philippe; Kincl, Laurel; Burstyn, Igor; Lavoué, Jérôme
Abstract : Objectives: The Integrated Management Information System (IMIS), with over 1M measurements taken by inspectors of the Occupational Safety and Health Administration, is an important source of information for occupational epidemiology. We assessed the association of the reason for conducting inspection with the reported levels of chemical exposure in IMIS. Method: Time weighted averaged measurements made during each of the un-programmed inspection types (employee complaint, referral by safety officer, follow-up, monitoring) were compared to those made during programmed inspections for 50 chemicals. Ratios of the median of detected results (dM), and the differences in the proportion of non-detects (dPr) for each category compared to the programmed inspections were calculated for each chemical. Results: The analysis included 218 916 measurement records. 32% were collected during programmed inspections, 48% – complaints, 13% – referral, 5% – follow-up, and 2% – monitoring. The detected concentrations were similar for complaint (dM=0.98, interquartile range across chemicals, IQR=[0.83;1.11]) and referral (dM=0.91, IQR=[0.76;1.08]) inspections and greater for follow-up (dM=2.18, IQR=[1.38;3.13]) and monitoring (dM=1.59, IQR=[1.24;2.44]) inspections relative to presumed representative inspections. Similarly, the proportion of non-detects were similar to programmed inspections during complaint-driven (dPr=3%, IQR=[-1;8]) and referrals (dPr=0%, IQR=[-6;5]) and lower during follow-up (dPr=-11%, IQR=[-19;-2]) and monitoring (dPr=-8%, IQR=[-12;3]) inspections. Conclusions: Despite the absence of consistent differences across chemicals for the most frequent categories, exposure levels during non-programmed surveys can be significantly higher than those obtained during presumably representative measurement campaigns. Great care has to be taken in determining typical exposure distributions from OSHA's IMIS data.